2013
DOI: 10.1080/07391102.2013.812520
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of 2-APB, dantrolene, and TDMT with IP3R and RyR modulates ER stress-induced programmed cell death I and II in neuron-like PC12 cells: an experimental and computational investigation

Abstract: Ca(2+) is an essential second messenger, playing a fundamental role in maintaining cell viability and neuronal activity. Two specific endoplasmic reticulum calcium channels, ryanodine receptors (RyRs) and inositol 1,4,5-trisphosphate receptors (IP3Rs) play an important role in Ca(2+) regulation. In the present study, we provided a 3D structure of RyR and IP3R by homology modeling, and we predicted their interactions with a known neuroprotective compound, 3-thiomethyl-5,6-(dimethoxyphenyl)-1,2,4-triazine (TDMT)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 57 publications
0
20
0
Order By: Relevance
“…Although dantrolene is an inhibitor of RyR 2 (Dulhunty et al ., ), a portion of the neurons, which had very low levels of basal [Ca 2+ ] i , responded with an increase in cytoplasmic [Ca 2+ ] i after adding 10 μ m dantrolene. We hypothesize that this discrepancy could be attributed to Ca 2+ release via IP 3 R Ca 2+ channels, which may be activated when the [Ca 2+ ] i is very low and RyR are blocked, as part of a homeostatic calcium control mechanism (Parys & De Smedt, ; Ansari et al ., ).…”
Section: Discussionmentioning
confidence: 97%
“…Although dantrolene is an inhibitor of RyR 2 (Dulhunty et al ., ), a portion of the neurons, which had very low levels of basal [Ca 2+ ] i , responded with an increase in cytoplasmic [Ca 2+ ] i after adding 10 μ m dantrolene. We hypothesize that this discrepancy could be attributed to Ca 2+ release via IP 3 R Ca 2+ channels, which may be activated when the [Ca 2+ ] i is very low and RyR are blocked, as part of a homeostatic calcium control mechanism (Parys & De Smedt, ; Ansari et al ., ).…”
Section: Discussionmentioning
confidence: 97%
“…Though only a few studies on the toxicity of boron go beyond boric and boronic acids, it is known that some boroles (Fan, 2010), boranes (Ruhaak, 2010;Crowe, 2015), borinic acids (Ansari, 2014;Soriano-Ursúa, 2014b) and BODIPY derivatives (Alford;) are considered quite poisonous compared to structurally related boron-free compounds (Duydu, 2015). On the other hand, these BCCs are probably advantageous agents for diagnosis and therapeutics.…”
Section: The Origins Of Avoidance Of Bccs In Medicinementioning
confidence: 99%
“…The understanding of the complex relationship between ER stress, autophagy and apoptosis has not been clarified until now. Previous studies demonstrated that ER stress regulates the apoptotic cell death and autophagic cell death [ 46 , 65 ]. When the cells expose to a mild stress, mild ER stress promotes neuroprotection via the activation of autophagy [ 46 , 65 ].…”
Section: Discussionmentioning
confidence: 99%